Comparison of guidelines for the use of TNF inhibitors for psoriasis in the United States, Canada, Europe and the United Kingdom: a critical appraisal and comprehensive review. (18th August 2018) - Shah, Vidhi V.; Lee, Erica B.; Reddy, Shivani; Lin, Elaine J.; Wu, Jashin J.
Abstract: Purpose: To compare and contrast evidence-based CPGs from leading dermatological organizations for the use of tumor necrosis factor inhibitors (TNFi) in psoriasis. Materials and methods: Guidelines from the British National Institute for Health and Care Excellence (NICE), the British Association of Dermatologists (BAD), the American Academy of Dermatology (AAD), the National Psoriasis Foundation (NPF), and the Canadian Dermatology Association (CDA) were reviewed and compared. Results: Various guidelines are similar regarding treatment initiation but have significant differences regarding topics such as continuous versus intermittent therapy, use in erythrodermic and pustular palmoplantar psoriasis and special patient populations. Conclusion: TNF inhibitors remain valuable tools in psoriasis therapy, and guidelines for their use may help clinicians use them effectively.